Спекание нанодисперсной керамики генетического происхождения (обзор) - Кайдаш, О.Н. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2010)
Numerous studies to obtain materials with the grains size of less than 1 μm for substantial
improvement of their properties have been investigated. Most efforts were directed to use pressure
during sintering: hot pressing [1; 2], hot isostatic pressing [1; 3] or spark plasma sintering [4; 5].
In the last decade has developed an efficient innovation method of sintering without pressure
named two-step sintering [6; 7].